2015
DOI: 10.3727/096368915x686760
|View full text |Cite
|
Sign up to set email alerts
|

Autologous adipose tissue-derived stromal vascular fraction cells application in patients with osteoarthritis

Abstract: Ahead of Print article withdrawn by publisher

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…Indeed, to date, clinical studies suggest that SVF and ATD-MSCs are safe and capable of tissue repairing [15, 18, 19, 29, 30]. Various well-defined harvesting techniques are available for liposuction procedure [27, 31, 32], even though there is not one method providing the best results in terms of viability and volume of adipose tissue with its cellular components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, to date, clinical studies suggest that SVF and ATD-MSCs are safe and capable of tissue repairing [15, 18, 19, 29, 30]. Various well-defined harvesting techniques are available for liposuction procedure [27, 31, 32], even though there is not one method providing the best results in terms of viability and volume of adipose tissue with its cellular components.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of symptomatic knee arthritis with ATD-MSCs proved effective with a single infusion [1519]; the efficacy of multiple infusions of ATD-MSCs in the articular joint is considered but still debated due to lack of data from clinical trials [19]. The availability of banking adipose tissue would allow treating with multiple infusions patients, avoiding repeated liposuction procedures for patients.…”
Section: Introductionmentioning
confidence: 99%
“…19 A total of 1856 joints mainly knee and hip joints were treated with a single dose of SVF cells and a follow up after treatment was done at 3, 6 and 12 months and found that 75% score improvement was found in 63% of the patients and at least 50% score improvement was noted in 91% of the patients after 12 months of after the therapy. 20 Adipose derived stromal vascular fraction (SVF), containing large number of cells. Adipose tissue-derived MSCs are more genetically stable in a long term culture, display a lower senescence ratio and higher proliferative capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-center case control study [10] Currently, there is no cure for painful OA in stages 2 and 3. For these patients, the intra-articular injection of ASCs can be an alternative treatment.…”
Section: Outcome and Commentsmentioning
confidence: 99%
“…Also, obtaining approximately 100 g of adipose tissue and percutaneous joint injections of ASCs with or without PRP are considered to be a minimally invasive procedure and can be readily accepted by patients [6]. These procedures carry a relatively low rate of morbidity and side effects [7][8][9][10].…”
Section: Outcome and Commentsmentioning
confidence: 99%